2009
DOI: 10.1007/s12640-009-9030-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Neuroprotective Effects of Rasagiline and Aminoindan with Selegiline on Dexamethasone-Induced Brain Cell Apoptosis

Abstract: Stress can affect the brain and lead to depression; however, the molecular pathogenesis is unclear. An association between stress and stress-induced hypersecretion of glucocorticoids occurs during stress. Dexamethasone (a synthetic glucocorticoid steroid) has been reported to induce apoptosis and increase the activity of monoamine oxidase (MAO) (Youdim et al. 1989). MAO is an enzyme for the degradation of aminergic neurotransmitters; dopamine, noradrenaline and serotonin and dietary amines and MAO inhibitors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 42 publications
2
35
1
Order By: Relevance
“…1, MAO B catalytic activity increased by ϳ2.8-fold in response to dexamethasone (a potent synthetic glucocorticoid hormone, 100 nM, 48 h) in 1242-MG cells. This is consistent with the observations as reported by other groups using different neuronal/glial culture systems (Carlo et al, 1996;Tazik et al, 2009). The concentrations of dexamethasone as used under current experimental conditions did not produce cytotoxicity, which was ensured in our previous study (Ou et al, 2006a).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…1, MAO B catalytic activity increased by ϳ2.8-fold in response to dexamethasone (a potent synthetic glucocorticoid hormone, 100 nM, 48 h) in 1242-MG cells. This is consistent with the observations as reported by other groups using different neuronal/glial culture systems (Carlo et al, 1996;Tazik et al, 2009). The concentrations of dexamethasone as used under current experimental conditions did not produce cytotoxicity, which was ensured in our previous study (Ou et al, 2006a).…”
Section: Resultssupporting
confidence: 93%
“…Hence, in this study, we used a human glioblastoma 1242-MG cell line as a model system to investigate the molecular mechanisms responsible for glucocorticoid activation of MAO B. 1242-MG cells express reasonable levels of MAO B and show responses to glucocorticoids in terms of the activation of GR (Tazik et al, 2009). First, we determined the effect of glucocorticoids on MAO B catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…(-)Deprenyl protected neuronal cells in cellular and animal models (Maruyama et al 1998;Kupsch et al 2001) and also showed disease modification in PD (Palhagen et al 2006). Rasagiline was reported to be more potent in protecting neuronal cells in cellular and animal models of evoked neuropathy than (-)deprenyl (Abu-Raya et al 2002;Tazik et al 2009). Also by clinical trials, rasagiline was proved to have a possible disease-modifying effect (Olanow et al 2009), even though the final conclusion for its neuroprotective effect of MAO-B inhibitors is still controversial (Riederer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Deprenyl is a selective inhibitor of monoamine oxidase type-B which is responsible for the oxidation of dopamine in the brain. MAO is an enzyme for the degradation of aminergic neurotransmitters; dopamine, noradrenaline and serotonin and dietary amines and MAO inhibitors are classical antidepressant drugs (Tazik et al 2009). Furthermore, by inducing antioxidant enzymes and decreasing the formation of reactive oxygen species, deprenyl is able to combat an oxidative challenge implicated as a common causative factor in neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%